A comparative analysis of biochemical markers of systemic inflammation in experimental models of acute and chronic organ damage in laboratory animals - Seniuk, Igor; Galuzinska, Liubov; Polovko, Nataliia; Loshakov, Anatolii; Strelchenko, Kateryna (ScienceRise: Biological Science, 2026)
Aim. The aim of the study was to determine and comparatively analyse the specified markers in models of acute and chronic inflammation of various localisation and genesis in laboratory animals. Materials and Methods. The study was conducted using models, such as adrenal myocarditis, tetrachloromethane hepatitis, UV erythema, folacin-induced nephropathy, and doxorubicin nephropathy. Results. The content of total protein, C-reactive protein, creatinine, urea, TBA-AP, as well as the activity of cytolysis enzymes ALT and AST in nephropathy models were determined. The results of experimental studies showed the heterogeneity of marker changes depending on the selected model. In the UV erythema model, the diameter of erythema, CRP, and ALT significantly increased, while the content of TBA-AP decreased against the background of experimental pathology. In tetrachloromethane hepatitis, there was an increase in the liver mass coefficient, CRP content, TBA-AP, ALT and AST activity, and a decrease in total protein. Adrenaline myocarditis was accompanied by an increase in cardiac mass index, CRP, TBA-AP and AST activity. In both models of nephropathy (folic acid and doxorubicin), the kidney mass index increased; creatinine and urea levels rose, while total protein levels decreased; CRP levels increased in the model of nephropathy caused by folic acid and doxorubicin, while TBA-AP levels and ALT and AST activity increased significantly. Conclusions. The experimental data obtained indicate a pronounced activation of systemic inflammation and oxidative stress in all model pathologies, but the degree and spectrum of changes in markers differ depending on the aetiological factor and organotropism of the pathologic process